PEMBUATAN BERAS ANALOG BERBASIS TEPUNG PISANG GOROHO (Musa Acuminate) DENGAN BAHAN PENGIKAT CARBOXYMETHYL CELLULOCE (CMC) - Gideon H. Putra; Erny J.N. Nurali; Teltje Koapaha; Lana E. Lalujan (COCOS, 2013)
ABSTRACTGoroho banana (Musa acuminate) is one type of banana plants that grow in North Sulawesi province and has a high nutrient content. Analog Rice is one of the solutions can be developed either in terms of the use of a new food source or to diversify food. The research objective is to get the right formulas of CMC in the manufacture of analog rice flour goroho . second stage of rice manufacturing are analog to the treatment CMC concentration subsitution. Organoleptic test results, treatment was continued with an analysis of selected physical properties. The results for the goroho banana flour yield of 40.10% and the color value of L (+) banana flour goroho : 80.33. For cooked rice analog lowest hardness level in treatment E = (98.4% banana flour goroho : 1.6% CMC) : 0.48 mm/g/sec and the chosen treatment CMC formula that treatment B = (99.6% flour banana goroho : 0.4% CMC). With the analysis of physical properties that yield: 23.18%, rice color : L (+)32.19, a*(+)5.92, b*(+)12.96, 221.729% water absorption, and time rehydration 20 minutes.Keywords: Banana goroho, analog rice, CMC.